Agricultura familiar e sua inserção nos mercados na bacia do Rio Xambrê-PR - Cordeiro, Eder Silva (2018)
Studies on markets and the insertion of family farming in market relations are a recent theme in relation to sustainable rural development processes. Thus, the objective of this research is to understand the insertion of family farmers in family farming markets in the Xambrê River Basin, Paraná. For this, three articles were prepared, the first of which analyzes the strategies and instruments of family farming that permeate the process of sustainable rural development in the Xambrê River basin. In the second, the types of markets accessed by farmers in the analyzed context were identified. And in the third article, a reflection on family farming, with access to markets and its relationship with environmental issues is addressed. It was possible to meet the objectives proposed in each of them, in which the reality and context of market access by family farming in the Xambrê River Basin can be highlighted. The methodology used was that of field research with the application of interviews and data tabulation. The results presented identify the need for organization by producers belonging to the Xambrê River Basin, opening up more spaces for marketing, organization of production regarding the diversification of products offered and new direction of cooperatives for the organization to achieve better prices, purchases advantages of inputs and, consequently, for farmers to obtain greater profitability.